Analysis of the Effect of Sea Salt, Volcanic Ash and Black Carbon Contamination on the Insulation Resistance of Porcelain Insulators - Yudia Meka Seftiani; Romi Mulyadi; zulka hendri; witri onanda; nofri dodi (Program Studi Teknik Elektro Universitas Khairun, 2026)
The reliability of porcelain insulators in power systems is strongly influenced by surface conditions, particularly contamination from environmental pollutants. Such contamination can significantly reduce insulation resistance, thereby increasing the risk of leakage currents and flashover. This study aims to analyze the effects of major pollutants—namely sea salt, volcanic ash, and black carbon—on the insulation resistance of porcelain insulators. An experimental approach was employed by testing insulators under clean conditions and comparing the results after artificial contamination with each pollutant under controlled temperature and humidity conditions. Insulation resistance was measured using a megohmmeter, and the data were processed using the arithmetic mean of ten repeated measurements and analyzed descriptively. The results show that the clean condition yielded the highest average insulation resistance of 518 MΩ. Sea salt contamination caused the most significant reduction (210 MΩ), followed by volcanic ash (240 MΩ) and black carbon (280 MΩ). The greater impact of sea salt is attributed to its hygroscopic nature, which forms a conductive electrolyte layer, while volcanic ash contributes through its mineral composition and moisture retention, and black carbon through conductive particle networks. It can be concluded that sea salt has the greatest impact on insulation resistance degradation, followed by volcanic ash and black carbon. Although the measured values remain within acceptable limits for medium-voltage systems, continuous contamination may increase the risk of insulation degradation. Therefore, appropriate maintenance and pollution control strategies are necessary to ensure long-term reliability.